The growing trend of scientific interest in sports science research - Lippi, G.; Guidi, G. C.; Nevill, A.; Boreham, C. (Journal of Sports Sciences, 2008)
There is a firm perception that the international scientific community is focusing more than ever on basic and applied research in sports science. Recognizing its inherent limitations (see Eston, 2005), the impact factor is still a valuable tool for evaluating scientific journals, and it is increasingly used also to assess trends in basic and clinical research worldwide (Garfield, 1999). After retrieving data of journals included in the "Sports Sciences" subject category of the ISI database from the year 2003 through 2006 (Thomson Scientific, 2007), it is noteworthy that the aggregate and median 2006 impact factors of these journals have increased by 20% and 32% respectively from those of 2003, and by 5% and 15% respectively from those of 2005. ...